APLIKASI MOVING AVERAGE FILTER PADA TEKNOLOGI ENKRIPSI - Hermawi, Adrianto (Universitas Tarumanagara, 2007)
A method of encrypting and decrypting is introduced. The type of information experimented on is a mono wave sound file with frequency 44 KHZ. The encryption technology uses a regular noise wave sound file (with equal frequency) and moving average filter to decrypt and obtain the original signal. All experiments are programmed using MATLAB. By the end of the experiment the author concludes that the Moving Average Filter can indeed be used as an alternative to encryption technology.